Field Effect Transistor Sensors Based on In‐Plane 1T′/2H/1T′ MoTe2 Heterophases with Superior Sensitivity and Output Signals. (5th August 2022) - Zhang, Shichao; Wu, You; Gao, Feng; Shang, Huiming; Zhang, Jia; Li, Zhonghua; Fu, YongQing; Hu, PingAn
Abstract: 2D materials, with their extraordinary physical and chemical properties, have gained extensive interest for physical, chemical and biological sensing applications. However, 2D material‐based devices, such as field effect transistors (FETs) often show high contact resistance and low output signals, which severely affect their sensing performance. In this study, a new strategy is developed to combine metallic and semiconducting polymorphs of transition‐metal dichalcogenides (TMDCs) to solve this critical issue. Such a phase engineering methodology to integrate large‐scale and spatially assembled multilayers of 2H MoTe2 FETs with coplanar metallic 1T′ MoTe2 contacts is applied. Such in‐plane heterophase‐based FETs exhibit an ohmic contact behavior with an extremely low contact resistance due to the coplanar and seamless connections between 2H and 1T′ phases of MoTe2 . These 1T′/2H/1T′ based FETs are successfully demonstrated for detecting NH3 with high current outputs increased up to microamp levels without using any conventional interdigital electrodes, which is compatible with the current CMOS circuits for practical applications. Furthermore, the as‐fabricated sensors can detect NH3 gas concentrations down to 5 ppm at room temperature. This study demonstrates a new strategy of applying the heterophase MoTe2 ‐based nanoelectronics for high‐performance sensing applications. Abstract : Compared to the other types of gas sensors, this 1T′/2H/1T′ device possesses distinctive advantages. First, the polycrystalline 2H MoTe2 provides numerous defects, such as vacancies, edges, and grain boundaries, which play crucial roles in enhancing the response rate and sensitivity of a gas sensor. Second, the low‐resistance planar heterostructure ensures a microamp scale current output even at larger channel aspect ratios.